Renovation of Goldfinch Bakeshop design elements that affect its marketability - Vallente, Anna Maria F. (College of Home Economics, University of the Philippines Diliman, 1992)
The researcher conducted the study primarily to improve the interior condition of Goldfinch Bakeshop focusing on the design elements that affected its marketability. Data gathering was done through the following: ocular survey, informal interview with the shop owner, photographic recording, analysis of blueprinted architectural plans and distribution of survey forms. A purposive selection of respondents was employed to limit the scope of the study to a small ratio of the community. The survey results pointed out the existing problems of the bakeshop which centered on the poor design layout. The data gathered were collated and analyzed to serve as the basis for the development of the design proposal which included an efficient floor plan and product layout.